ANALISIS PENERAPAN STANDART OPERATIONAL PROCEDURE (SOP) DALAM PELAYANAN KESEHATAN BERBASIS IT MENGGUNAKAN ANALISA SWOT - Retnasari, Tri (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2014)
Hospital at this time in the form of systems utilizing information technology support, with the a im to facilitate the activities, one of which is Pengayoman Cipinang Hospital. Hospital system in Pengayoman Cipinang still a stand-alone system, separate, and the scopeis limited to the organization al unit that is less supportive use of hospital services. To over come this, the design is made of information technology architecture as a referral hospital for the construction of integrated information systems. This study is the proposal for information technology governance Pengayoman Cipinang Hospital as a referral for Pengayoman Hospital Cipinang to eliminate the difference of both the existing situation and reaching a state of the target architecture. As one of the agencies engaged in health, have not been fullyable to provide complete informations o as to develop an information system that refers to the Standard Operating Procedure (SOP) in the field of health care is necessary to design a good information system architecture. Analysis of IT Governance using SWOT method. Keywords:Hospital, Standard Operational Procedure (SOP), SWOT.